Analysis of The Effect of Company Characteristics and Corporate Governance on Tax Aggressiveness: Before and During The Covid-19 Pandemic (Empirical Study of Manufacturing Companies Listed on The Indonesia Stock Exchange Period 2019-2020) - Saputri, Risma Talia; Handayani, Rr. Sri (Universitas Muhammadiyah Surakarta, 2023)
This study aims to analyze the effect of company characteristics and corporate governance on tax aggressiveness before and during the Covid-19 pandemic. The independent variables of this study are the company characteristics (profitability, capital intensity, inventory intensity, and company size) and corporate governance (independence the board of commissioners and audit committee size). The dependent variable of the study is tax aggressiveness measured using the Effective Tax Rate (ETR). The population of this study are manufacturing companies listed on the Indonesia Stock Exchange period 2019-2020. The sampling method used was purposive sampling and obtained a total sample of 176 firm-years of observation with certain criteria. This study uses multiple regression analysis and chow test with SPSS 25 software. Based on results of the t-test, there was a positive effect profitability on tax aggressiveness before and during the pandemic, there was a positive effect company size on tax aggressiveness before the pandemic, there was a negative effect audit committee size on tax aggressiveness before and during the pandemic. However, it is not proven company size had an effect on tax aggressiveness during the pandemic. Meanwhile, capital intensity, inventory intensity, and independence the board of commissioners have not been shown an impact on tax aggressiveness before and during the pandemic. Then, the findings chow test found there was no difference effect of the six independent variables on tax aggressiveness before and during the pandemic.